Correlation of Olx Indonesia Television Advertising Exposure and Intensity of Peer Group Communication with Desire of Transacting in Olx.co.id - Rahman Zulhardi, Alfin; Herieningsih, MS, Dra. Sri Widowati (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2016)
Advertising is one of the most efffective way to inform audience about the products. Olx Indonesia television advertising exposure potentially related to desire of transacting in Olx.co.id. Intensity of peer group communication about transacting in Olx.co.id also potentially related to desire of transacting in Olx.co.id. This study aims to determine the correlation of Olx Indonesia television advertising exposure and intensity of peer group communication with desire of transacting in Olx.co.id. The rational used is the Advertisig Exposure Theory and How peer group affect consumer behaviour. This type of research is explanatory research, using technique of Non-probability sampling with accidental sampling method to determine the sample. The total sample of 100 respondent who have seen Olx Indonesia television advertising aged 15 – 25 years old in the city of Semarang. Analysis of the data used is Pearson correlation SPSS. The first hypothesis test results show that the variable Olx Indonesia television advertising exposure (X1) is not correlated to desire of transacting in Olx.co.id (Y) and showed no significant results, with the result Sig/significance worth 0.588 or greater than 0,05. The second hypothesis test showed intensity of peer group communication (X2) is correlated to desire of transacting in Olx.co.id (Y), with the result Sig/significance worth 0.002 or less than 0.05. Advice can be given is OLX Indonesia can do another promotion as using Social Media to reach audience directly, especially teenagers, considering direct communication has more positive impact to desire of transacting in Olx.co.id.